Application Of Transmission-Mode Ultrasonic Tomography To Identify Multiphase Flow Regime - Yasmin, Abdul Wahab (2011)
This paper presents an application of ultrasonic tomography where the main objective is to identify the multiphase flow regime which is liquid, gas and solid at once. The system was designing non-invasively by using offline method. The transmission mode with fan shaped beam back projection had been implemented for sensing purposes where 8x8 projections were produced. Beside, the linear back projection (LBP) algorithm was implemented in the software system for the image reconstruction part. Experiments show that the multiphase flow regime for liquid, gas and solid at once can be identifying by using ultrasonic tomography. The results of experiments and possible future improvement were also discussed.